1994
DOI: 10.1063/1.111383
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties near the band gap on hexagonal and cubic GaN

Abstract: We have measured the photoluminescence and optical reflection spectra of cubic and hexagonal GaN films epitaxially grown on GaAs and 3C-SiC substrates by gas-source molecular beam epitaxy using microwave-activated NH3 source. The crystalline quality of the epilayers was improved by using an activated NH3 beam and 3C-SiC substrates, which enabled us to obtain intense optical signals. The measured spectra suggest that the band gap of cubic GaN is around 190 meV smaller than that of hexagonal GaN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…In Table 2, we summarized the band gap energies for the studied materials. Our results were parallel to the theoretical [20,21] and experimental [ [22][23][24][25] values. The band gap energy of GaAs 1−y N y shows unexpected and drastic decrease with increasing N concentration in low N composition region and shows a nonlinear tendency for whole N concentration.…”
Section: Electronic Propertiessupporting
confidence: 91%
“…In Table 2, we summarized the band gap energies for the studied materials. Our results were parallel to the theoretical [20,21] and experimental [ [22][23][24][25] values. The band gap energy of GaAs 1−y N y shows unexpected and drastic decrease with increasing N concentration in low N composition region and shows a nonlinear tendency for whole N concentration.…”
Section: Electronic Propertiessupporting
confidence: 91%
“…In Table 2, we summarized the band gap energies for the studied materials. Our results are parallel to the theoretical [12], [19] and experimental [20][21][22][23] values. The band gap energy of GaAs 1-x N x shows unexpected and drastic decrease with increasing N concentration in low N composition region and shows a nonlinear tendency for whole N concentration.…”
Section: Electronic Propertiessupporting
confidence: 78%
“…Cubic GaN was grown on GaAs (001) substrates and hexagonal GaN on (111) substrates. Okumura et al 16 observed carbon contamination of MBE grown GaN using DMHy.…”
Section: Introductionmentioning
confidence: 98%